Centennial black carbon turnover observed in a Russian steppe soil - K. Hammes (Biogeosciences, 2008)
Black carbon (BC), from incomplete combustion of fuels and biomass, has been considered highly recalcitrant and a substantial sink for carbon dioxide. Recent studies have shown that BC can be degraded in soils. We use two soils with very low spatial variability sampled 100 years apart in a Russian steppe preserve to generate the first whole-profile estimate of BC stocks and turnover in the field. Quantities of fire residues in soil changed significantly over a century. Black carbon stock was 2.5 kg m−2, or about 7–10% of total organic C in 1900. With cessation of biomass burning, BC stocks decreased 25% over a century, which translates into a centennial soil BC turnover (293 years best estimate; range 182–541 years), much faster than so-called inert or passive carbon in ecosystem models. The turnover time presented here is for loss by all processes, namely decomposition, leaching, and erosion, although the latter two were probably insignificant in this case. Notably, at both time points, the peak BC stock was below 30 cm, a depth interval, which is not typically accounted for. Also, the quality of the fire residues changed with time, as indicated by the use benzene polycarboxylic acids (BPCA) as molecular markers. The proportions of less-condensed (and thus more easily degradable) BC structures decreased, whereas the highly condensed (and more recalcitrant) BC structures survived unchanged over the 100-year period. Our results show that BC cannot be assumed chemically recalcitrant in all soils, and other explanations for very old soil carbon are needed.